Creating contemporary mythical creature identities in Super Deformed (SD) style to promote awareness of Thai art and culture among Gen Z - เชื่อมสุข ปณัญภพ; ฤกษ์สมุทร ปฐมพงษ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
Creating contemporary identities of Himmapan Creatures in the SD (Super Deformed) style to promote the awareness of Thai art and culture among Gen Z. This research aims to 1) study the distinctive visual characteristics of Himmapan Creatures and the principles of designing SD (Super Deformed) characters, 2) create and design contemporary SD (Super Deformed) characters of Himmapan Creatures with a distinctive and accessible identity, and 3) study the satisfaction and perception of the Gen Z target group toward the design of contemporary SD (Super Deformed) characters of Himmapan Creatures. The research was conducted using a creative research approach, starting with the analysis of documents and information on Himmapan Creatures and selecting and processing them through simplification, proportion adjustment, and colorization to make them contemporary and aligned with the target group’s tastes. The research findings indicate that SD (Super Deformed) character design can effectively increase Gen Z’s interest in Thai art and culture. This is achieved through emphasis on head-to-body ratios of 1:2 or 1:3, the use of curved lines to create a friendly feel, and the use of bright, modern color palettes while maintaining the unique identity of each animal. Expert evaluation of the design quality showed the works to be highly suitable. Furthermore, a satisfaction survey among Gen Z revealed high satisfaction with the aesthetics and the communication of contemporary Thai culture. This demonstrates that SD character design is an effective tool for bridging the cultural gap and promoting awareness of Thai art and culture among younger generations.